Respon Pertumbuhan dan Hasil Padi Sawah (Oryza Sativa L.) Varietas Inpari 33 Akibat Kombinasi Pupuk Organik dan Anorganik N, P, dan K - Ilham Putra Anugrah; Sulistyo Sidik Purnomo; Kasdi Pirngadi; Zuziana Susanti (Peneliti.net, 2022)
The continuous use of inorganic fertilizers without the application of organic fertilizers can cause nutrient imbalances in the soil, low fertilization efficiency, damage to soil structure, and low soil microbiology. This experiment was conducted in Experimental Station of Indonesia Center for Rice Research Sukamandi Jaya Village, Subang District, West Java from July to November 2020. The objective of the experiment was to find out of N, P, K and organic fertilizer that gave the best yield on growth and yield of rice (Oryza sativa L.). The research was used experimenthal method it was arranged in split plot design with 6 threatment and 4 replications. As the main plot was N, P, K fertilizer, consist of 4 threatment of fertilizer: P1 (kontrol), P2 (+PK), P3 (PHSL), P4 (NP), P5 (+NK), and P6 (+NPK). As subplot was organic fertilizer: B1 (2 ton/ha), B2 (compost rice straw 5 ton/ha), and B3 (control). The effect of treatment is analyzed with variety analysis and if the F test is 5% significant, then to find out the best treatment continued with further DMRT tests (Duncan Multiple Range Test). The results showed that there was an interaction between the provision of inorganic and organic fertilizers to the height of plants aged 35 days after planting and 1000 grains weight. Meanwhile, at the height parameters of plants aged 21 days after planting, 57 days after planting, 64 days after planting, and 84 days after planting, number of tillers, number of panicles per hill, number of grains, and the grain yield there are real influences independently. The highest grain yield of 4,84 Kg/tile (6,45 tons/ha) was achieved by P5 (+NK) treatment and was not real different from P3 (PHSL), P4 (+NP), and P6 (+NPK) treatment with consecutive weights of 4,82 Kg/tile (6,43 tons/ha), 4,44 Kg/tile (5,92 tons/ha), and 4,46 Kg/tile (5,95 tons/ha).